The university and extensionist training - Menacho-Mallqui, Tomas (2023)
The extensionist’s activity is the transfer of technology aimed at promoting innovations in the farmer's space, which plays an important role in increasing income, improving the farmer's quality of life and improving rural development. The purpose of this article is to describe actions to guide the improvement of the extensionist's training and activity, according to the social demands, after the COVID-19 pandemic. Therefore, we consider that the university training process requires the development of flexible  competences among students, providing them with new insertion spaces to be protagonists of the development process of rural communities and thus avoiding the adoption of the traditional extension system. In this sense, it is opportune to have the necessary proposals and tools to guide extensionists to obtain a real diagnosis, a plan of participatory actions and insertion in the feld, promoting sustainable rural development